A Theory on the Relativity of Factors Impacting the Utilization of Medical Information Services From the Pharmaceutical Industry. (September 2016) - Albano, Dominick; Soloff, Allison; Heim, Katelyn; Mavila, Sudeep
Health care providers have many options for obtaining answers to their questions about pharmaceutical products. These options include drug information curators and aggregators such as ePocrates, WebMD, and Wikipedia, as well as professional journals. However, drug information obtained directly from a pharmaceutical company is arguably the best source of information regarding that company's medicine. This is because medical information (MI) professionals from the pharmaceutical industry have the product expertise, technical skills, and access to relevant information that enable current, evidence-based, and scientifically accurate information to be provided. Further, it is reasonable to assume that "good" information leads to better patient decisions and therefore better patient outcomes. Several factors are implicated in the use of a pharmaceutical company's medical information resource. These factors include, but are not limited to, awareness of the availability of the resource, ease of access, and trust of the information. In this paper, the authors discuss the relevance of these factors and propose an integrated relational theory (referred to as the "MI Theory of Relativity") to model the utilization and value of a medical information service.